2016
DOI: 10.19082/3057
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of serum homocysteine, folic acid, and vitamin B12 in patients complicated with preeclampsia

Abstract: IntroductionIncreased plasma homocysteine may be associated with adverse pregnancy outcomes, such as preeclampsia. The aim of this study was to determine the plasma homocysteine, serum folate, and vitamin B12 levels in preeclamptic pregnant women.MethodsThis case-control study was conducted in 2016 in Ahwaz on 51 pregnant women with preeclampsia and 51 healthy pregnant women of the same gestational age, who served as controls. The case group also was subdivided into severe and non-severe preeclampsia. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 21 publications
(35 reference statements)
1
13
0
2
Order By: Relevance
“…Folate and VB12 are two vital regulators of the metabolism of Hcy [43]. A significant association is observed between maternal lower folate concentrations and higher Hcy levels as well as an increase in the risk of preeclampsia [44]. Furness et al [45] found that pregnant women with decreased red blood cell folate concentration and increased plasma concentrations of Hcy at 18-20 weeks of gestation had a higher risk of developing IUGR compared with controls (P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Folate and VB12 are two vital regulators of the metabolism of Hcy [43]. A significant association is observed between maternal lower folate concentrations and higher Hcy levels as well as an increase in the risk of preeclampsia [44]. Furness et al [45] found that pregnant women with decreased red blood cell folate concentration and increased plasma concentrations of Hcy at 18-20 weeks of gestation had a higher risk of developing IUGR compared with controls (P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Folate and vitamin B12 serum levels were described as unchanged [132,134,135] in PE when comparing to normotensive healthy women with uncomplicated pregnancies. However, opposite results indicating these vitamins deficiencies were also reported [135,146]. Nevertheless, further studies are needed to confirm whether the prescription of these vitamins could decrease serum homocysteine, thereby possibly reducing the risk of preeclampsia or (if it occurs) its severity.…”
Section: No Adma and Homocysteine In Preeclampsiamentioning
confidence: 97%
“…Still, most of the papers focus on the third trimester [93,130,132,133,134,135,137], where the differences between HHcys in severe and non-severe PE are marked. Pregnant women complicated with severe preeclampsia displayed significantly higher serum Hcy levels than with non-severe form [93,112,132,134,136,146]. Thus, homocysteine concentrations positively correlating with the clinical presentation of disease may constitute a marker of severity of preeclampsia.…”
Section: No Adma and Homocysteine In Preeclampsiamentioning
confidence: 99%
“…Previous studies have shown that Hcy concentration correlates with sperm, oocyte, and embryo qualities . Among 269 infertile women at a mean age of 37 ± 4 years, there were 69% presenting adequate plasma Hcy levels, and the pregnant women complicated with preeclampsia had significantly higher serum Hcy levels than healthy pregnant women at the same gestational age ( P < .001) . In addition, Hcy is reported to be inversely associated with fertility outcome, and lower Hcy levels have been found to correlate with a better chance of clinical pregnancy and better embryo grades in assisted reproductive technology (ART) .…”
Section: Introductionmentioning
confidence: 99%